PEMETAAN CAKUPAN TREATMENT COVERAGE TUBERKULOSIS PARU DI KABUPATEN BADUNG PADA TAHUN 2022 - Mas Andhita Dewi, I Gusti Ayu Agung; Kardiwinata, Made Pasek (ARCHIVE OF COMMUNITY HEALTH, 2025)
Treatment Coverage (TC) is the number of TB cases treated and reported in a given year divided by the estimated number of incident TB cases in the same year and expressed as a percentage. TC achievement in Badung Regency only reached 22.7% in 2021 of the national target of >85%. This study aims to map TC achievements in Badung Regency and the factors that influence low TC achievements in Badung Regency in 2022 using a Geographic Information System (GIS). This research is a type of analytic research using ecological studies. The sample in this study was the detection and treatment of pulmonary TB cases in each health facility in the working area of the puskesmas in Badung Regency in 2022 with 563 case findings.The results showed that spatially, low TC achievements were followed by low pulmonary TB case detection and occurred in areas with high population density. The number of active cadres is also related to TC achievements. The highest TC achievement was at Puskesmas II Petang, which was 100%, while the lowest TC achievement was at Puskesmas II Abiansemal, which was only 5%. To improve TC achievements, it is hoped that the activity of cadres will be increased so that there will also be an increase in the detection of existing TB cases. Keywords: Tuberculosis, Mapping, Treatment Coverage (TC)